Ouvertures et tensions liées à la conception d'un système d'évaluation en langues, numérique, multilingue et en ligne, dans une perspective communicative et actionnelle - Cristiana Cervini; Marie-Pierre Jouannaud (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
In this paper, we grapple with the problem of what it means for a placement test to be communicative or even "action-oriented" (CEFR, 2001). Communicative tasks ("any purposeful action considered by an individual as necessary in order to achieve a given result, an obligation to fulfil or an objective to be achieved", ibid.: 10) are especially difficult to translate into short, self-correcting assessment tasks. We explain how this difficulty was dealt with when we operationalized the construct of a multilingual online formative assessment tool (Self, "Système d'évaluation en langues à visée formative"), using among others the concepts of situational and interactional authenticity (Bachman & Palmer, 1996; 2010). Self is being developed as part of the Innovalangues project at Stendhal University, Grenoble, France (Masperi, 2012).